Optimasi Peran Guru Pendidikan Agama Islam dalam Pembelajaran Fikih: Dampaknya terhadap Pemahaman Agama - Kadi, Titi (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2023)
This article discusses the role of Islamic Religious Education teachers in deepening the study of Fiqh (Islamic jurisprudence) in junior high schools, with a focus on the methods they employ and their impact on students, as well as the implications for religious understanding and character development. The research utilizes a qualitative approach with data collection techniques including interviews, observations, and document analysis. The data is analyzed through data condensation, data presentation, and verification/conclusion stages. The research findings reveal the following: The role of PAI teachers includes acting as discussion facilitators, guiding students in case studies, and organizing simulations of religious worship and transactions. PAI teachers' efforts in teaching involve encouraging students to ask questions and engage in discussions on complex Fiqh matters, conducting practical activities such as group discussions, case studies, and religious worship simulations. The impact of PAI teachers' role in deepening Fiqh studies helps students attain a deeper understanding of Islam, enhances moral awareness, improves decision-making abilities, and fosters critical thinking skills. Implications of the role of PAI teachers in Fiqh education include the enhancement of religious understanding within society, the development of improved skills in interpreting Islamic law, the potential for ethical and responsible leadership, and the promotion of intercultural dialogue and religious tolerance. The implications of this study underscore the significance of effective PAI teachers in shaping a more knowledgeable, ethical, and value-committed younger generation.